Assessment of risks in the system of air traffic - Чинченко, Ю.В. (Proceedings of National Aviation University (archive), 2008)
Methods of control of hazards and risks sources in Air Traffic Management system are analysed. Principles of estimation of mid-air collision of aircraft on parallel airways at air traffic control are considered.